2005
DOI: 10.1080/02615470500096951
|View full text |Cite
|
Sign up to set email alerts
|

‘Placements Online’: Student Experiences of a Website to Support Learning in Practice Settings

Abstract: Social work practice and education in many parts of the world are implementing an elearning agenda. This article considers the experiences of students using a website developed to support learning in agency settings to discover if and how it can be used to create a 'bridge' between the learning environments of the university and practice. The website contains a range of features, including downloadable practice assessment documents, links to university based teaching units, electronic personal notification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Some studies that report on student perceptions of online courses, indicate that students are positive about e-learning feeling that they learnt from the collaborative and reflective interaction with other students (Littlefield and Roberson 2005;Quinney 2005;RobertsDeGennaro et al 2005). The sharing of information through online discussion forums has been a source of support for students involved in practical social work placements (Quinney 2005;Roberts-DeGennaro et al 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Some studies that report on student perceptions of online courses, indicate that students are positive about e-learning feeling that they learnt from the collaborative and reflective interaction with other students (Littlefield and Roberson 2005;Quinney 2005;RobertsDeGennaro et al 2005). The sharing of information through online discussion forums has been a source of support for students involved in practical social work placements (Quinney 2005;Roberts-DeGennaro et al 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Some research studies define elearning as an effective way for enhancing the individual's problem-solving skills [6,32,33]. The studies reported that collaborative learning reflects the interaction with other learners in the formal knowledge-retrieving environment, such as recommender technology, to know their learning goals and support them to be involved in practical work placements [34]. Recommender technology is a part of information retrieval [35].…”
Section: Literature Backgroundmentioning
confidence: 99%
“…It was found that the discussion board was used extensively as a means of continuing collaborative learning relationships that students had established before they began their placement as well as organising and planning academic assignments. Quinney (2005) reports that very little in-depth discussion occurred online, however, and that the students said that this took place when they spoke to each other instead. A requirement to show evidence of reflection and critical analysis in their online interaction as part of their course assessment might result in an improvement in the depth of the postings in the future.…”
Section: Introductionmentioning
confidence: 99%
“…A requirement to show evidence of reflection and critical analysis in their online interaction as part of their course assessment might result in an improvement in the depth of the postings in the future. Quinney (2005) also identifies a valuable topic for future research as she makes the point that a detailed examination of the views of the students who did not use the discussion forum would have provided valuable insights. Stracke (2007) has examined this area and focused her research on the students who dropped out of a blended language learning programme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation